Hybrid Efficient Stream Cipher KeyGenerator Based on LFSR’s and Chaotic Map - H. Abbaas, Dina; A. AbdulSalam, Ayad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Communication security that depends on chaos can be considered as a new approach which provides protection and security of communications and maintains confidentiality because Chaos theory can be implemented in cryptosystem successfully. A stream cipher, on the other hand, is a type of symmetric cryptosystem in which the plaintext is divided into small entities known as characters. The key in stream cipher is typically generated by a random bit generator. Many key stream generators employ linear feedback shift registers (LFSRs). LFSR systems are made up of a group of LFSR units and a combining function (CF) unit. The plaintext is encrypted one bit at a time. The key is fed into a random bit generator, which produces a long series of binary signals. This "key-stream" k is then combined with plaintext m, typically via a bit-wise XOR (Exclusive-OR modulo 2 addition), to produce the ciphertext stream, which employs the same random bit generator and seed. In this paper we will introduce a new stream cipher keygenerator which using a hybrid between chaotic and combination of Linear Feedback Shift Registers (LFSR’s). The proposed generator can be used to protect different types of data files (text, image, audio and video). Many kinds of tests are applied to specifying the goodness of the proposed keygenerator. The results of testing prove the efficiency of the suggested system.